On nonlinear thermo-electro-elasticity - Mehnert, Markus; Mokarram, Hossain; Steinmann, Paul (Proceedings of the Royal Society A-Mathematical Physical and Engineering Sciences, 2016)
Electro-active polymers (EAPs) for large actuations are nowadays well-known and promising candidates for producing sensors, actuators and generators. In general, polymeric materials are sensitive to differential temperature histories. During experimental characterizations of EAPs under electro-mechanically coupled loads, it is difficult to maintain constant temperature not only because of an external differential temperature history but also because of the changes in internal temperature caused by the application of high electric loads. In this contribution, a thermo-electro-mechanically coupled constitutive framework is proposed based on the total energy approach. Departing from relevant laws of thermodynamics, thermodynamically consistent constitutive equations are formulated. To demonstrate the performance of the proposed thermo-electro-mechanically coupled framework, a frequently used non-homogeneous boundary-value problem, i.e. the extension and inflation of a cylindrical tube, is solved analytically. The results illustrate the influence of various thermo-electro-mechanical couplings.
Keywords: electro-mechanical problem; thermo-mechanical problem; nonlinear elasticity; electro-active polymers; thermo-electro-mechanical coupling